The Effect of Application Quality, Electronic Word of Mouth and Service Quality on Purchase Decision of Shopee Consumers - tanjung, jasminia; Effendi, Junko Alessandro (PERFORMA, 2022)
The e-commerce industry that develops rapidly in Indonesia makes this thing as the main support in Indonesian economy, even more with the existence of pandemic, it makes people shift to digital platform. One of the payment system digitalization that becomes option for Indonesian people to purchase and look for product needs, that is, through e-commerce during pandemic. Shopee is the most frequent marketplace and is being used commonly by Indonesian people. The emerge of new competitors makes the competition of e-commerce industry tighter, this competition requires e-commerce to pay attention to several main factors that have important role for the existence and development of the company. Therefore, the researcher uses variables that include application quality, electronic word of mouth and service quality as factors that are able to affect consumers’ purchase decision by using Shopee e-commerce. This research is done quantitatively, with research sample by using purposive sampling technique of 220 respondents. Data collection is done by distributing online questionnaire, then hypothesis is done by hypothesis test and statistical test. The result of this research indicates that application quality, electronic word of mouth and service quality are variables that affect purchase decision.